AN EFFECTIVENESS OF INTERNET MEDIA AS A LEARNING RESOURCES TO STUDENT LEARNING ACHIEVEMENTS IN PSICHIATRIC NURSING LESSONS AT NURSING DEPARTMENT OF HEALTH POLYTECHNIC OF MATARAM - Eka Rudy Purwana; Muhamad Hasbi (Jurnal Kesehatan Prima, 2018)
Abstract: The development of science will trigger the development of technology. Conversely, the development of technology will also be able to improve the development of science. This development has altered the paradigm of the public to find and obtain information, which is no longer limited to information newspapers, audio and electronic, but also other sources of information and one of them is the internet network. Media has an important role in a learning process. Learning has changed from lecturing method to the use of the media in learning in order to increase the learner’s motivation, stimulate the learner to memorize what has been learnt, enable the learner to give feedback and encourage students to always pay attention to the material delivered. (Munadi, 2008: 9). One of the popular media now is the internet. This research was quantitative with Pre-Experimental design of One-Group Pretest-Posttest Design. The population was all students in the first grade and second semester of Diploma IV Mataram of Nursing Department, while the sample was 148 respondents. The statistical test used was Paired T test. The result indicated that the difference of pre and post test knowledge of classical learning group was P = 0,00, P value <0,005 which mean there is a significant difference between pre test knowledge and post test in classical learning group.Keywords: Learning achievement; Internet.